PENGARUH TEAM WORK DAN ORGANIZATION LEARNING TERHADAP KOMITMEN ORGANISASI KEPALA SEKOLAH SMP NEGERI DI KOTA MATARAM - Suhardi, Muhammad (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2019)
The purpose of this research is to determine the effect of Team Work and Organization Learning on Organization’s Commitment in this study middle high school in east Jakarta. The research methodology was survey which were selected by simple random sampling technique. Analysis and interpretation of the data indicate that (1)Team Work has a positive direct effect in Organization’s Commitment, (2) Organization Learning has a positivedirect effect in Organization’s Commitment, (3) Team Work has a positive direct effect in Organization Learning.   Keywords: Team Work, Organization Learning, Organization’s Commitment